Chemical Composition, Antimicrobial, Cytotoxic and Antiplasmodial Activities of Three Sponges from Buton Islands, Indonesia - Putra, Masteria Yunovilsa; Hadi, Tri Aryono (Marine Science Department Diponegoro University, 2017)
GC-MS analysis of the crude extracts of three different species of Indonesian marine sponges has been carried out for identification of bioactive compounds. The GC-MS analysis from Haliclona (Gellius) sp., Lamellodysidea herbacea, and Spheciospongia inconstans revealed the presence of 23, 21, 19 various compounds, respectively and mainly sterols and fatty acids. All the sponge species has been evaluated for antimicrobial activities, cytotoxicity using brine shrimp lethality bioassay and heme polymerization inhibitory activity assay for antiplasmodial activity. In this study, all the sponge species showed antimicrobial activities against at leastone of the test strains. Among them, the extract of sponge Lamellodysidea herbacea displayed activity against two Gram-positive bacteria (S. aureus and B. subtilis) and the Gram-negative bacteria V. cholerae, with inhibition zones of 10.3, 9.2 and 9.5 mm, respectively. The sponge Haliclona (Gellius) sp., showed significant activity against fungal pathogen C. albicans. The sponge Haliclona (Gellius) sp., displayed the ability to inhibit heme polymerization indicating an anti-Plasmodium function and also showed potent cytotoxic activity against the brine shrimp Artemia sp. Keywords: GC-MS analysis, antimicrobial, sponges,bioactive